Study on clinical profile of dengue in a tertiary care hospital of Nepal - Gyawali, Kenopama; Rijal, Reisha; Regmi, Shanti; Sedhai, Sabina; Adhikari, Shital (Journal of Chitwan Medical College, 2018)
Background: This study was conducted to elucidate the clinical features, laboratory parameters and management outcome of dengue patients admitted in a tertiary care center of Nepal. Methods: This was a retrospective descriptive study in dengue patients aged 12 years or more who were admitted in Tropical Wards and Intensive Care Unit of Chitwan Medical College Teaching Hospital (CMCTH), Chitwan, Nepal from November 2016 to December 2017. Diagnosis of dengue was confirmed by positive NS1 antigen or ELISA IgM or both. The required data were retrieved from patient’s medical records and laboratory data base. Data analysis was performed by using IBM-SPSS 20. Results: Of 60 patients, majority (65%) were male. Forty-one (68.33%) patients were diagnosed by positive NS1 and 18 (30%) were ELISA IgM positive. In the year 2017, highest numbers of cases (20, 33.33%) were in the month of November, followed by 14 cases (23.33%) in October. Similarly, in the year 2016, dengue cases peaked in the month of November. All patients had fever as a presenting complaint. Other common presenting features were myalgia 42 (70%) and headache 32 (53%). Thrombocytopenia was observed in 52 (86.66%) patients followed by leucopenia in 41 (68.33%) cases. Elevation of AST and ALT were found in 45 (75%) and 38 (63.33%) patients respectively. Only 2 patients (3.3%) had dengue with warning signs. Four (6.8%) patients needed platelet transfusion. No mortality was observed. Conclusions: Majority of dengue patients had thrombocytopenia, leucopenia, and elevated AST and ALT. Only two patients had dengue with warning signs. Hospital mortality was not documented.